The impact of the pandemic on the prevalence of depression from the perspective of fear of the SARS-CoV-2 community on physically active elderly (Research, Society and Development, 2022)
In March 2020, the World Health Organization declared a pandemic due to the new coronavirus. As a strategy to contain the spread of the disease and its spread, the government implemented restrictive measures, highlighting social isolation. However, measures like this can bring harm, so the study aimed to analyze the fear of contracting SARS-CoV-2 and the manifestation of depression, under the influence of the post-social isolation period, in physically active elderly women in the community. Methods: Anamnesis was carried out on the main possible changes in health conditions, then the COVID-19 fear scale and the geriatric depression scale were used. Thirty-four elderly women participated in the study. Results: among the participants in the sample, 12 (36%) were diagnosed with the disease of COVID-19, 10 (29.4%) had symptoms suggestive of a diagnosis of depression and 28 (82.4%) participants indicated that they suffered with little fear. of COVID-19. Conclusion: the elderly in the research had higher rates of depression and low levels of fear of COVID-19 during the collections, consequently, of the pandemic, however, there was no positive correlation between the variables.